Spatiotemporal distribution of soil moisture in gully facies - Seyed Hamidreza Sadeghi; Gholam Ali Ghaffari; Abdulsaleh Rangavar; Zeinab Hazbavi; Vijay P. Singh (International Soil and Water Conservation Research, 2020)
Gully erosion is one of the most important forms of land degradation in many regions of the world. Understanding the process of gully erosion therefore is important for better management of the watersheds prone to gully erosion. However, many different aspects of gully erosion, like hydrological behavior, are still not fully understood. The present study investigates the spatial distribution of soil moisture content (SMC), as one of the hydrological factors, at different depths and points across the cross section in the vicinity of the headcut of three gullies located in the Kalat County, Khorasan Razavi Province, Iran. SMCs were measured at depths of 10, 20, 30, 50, 70 and 100 cm at each seven points across the study cross sections one to three days after occurrence of three rain events. Two sampling points were symmetrically located at a distance of 50 cm outside the gully banks, two at the vertex of the sidewalls, two in the middle of the sidewalls and one at the center of gully cross section. SMCs were measured using a weighted method. Results of the study revealed a broad range of changes in SMCs at various depths and points. The minimum and maximum SMCs were found to be about 2% and 38%, respectively, for the study period and gullies under consideration. The coefficient of variation (CV) had drastic changes for various gullies and storm events from 2 to 107%. Results further indicated that SMC moved from the sidewalls towards the floor of the cross section. Accordingly, the maximum SMC for storm events was associated with the point located in the center of gullies, which indicated the role of gully system in draining soil moisture. The findings of this study will help watershed managers understand the important role of gully facies in changing water content of the soil that affects other ecohydrological processes. Keywords: Soil moisture capacity, Soil water, Subsurface runoff, Water erosion